Analysis of Consumer Interest Trends in Sustainable Products: A Longitudinal Study Based on Google Trends Data (2020–2025) - Muhammad Arwani; Nurkholifatul Maula; Musa Musa (Journal of Islamic Economic Development, 2025)
This study investigates the evolution of consumer interest in sustainable products in Indonesia through a longitudinal analysis of Google Trends data from 2020 to 2025. Amidst rising environmental concerns and the global push for sustainable development, this research utilizes digital big data to map the Search Volume Index (SVI) for keywords such as eco-friendly, organic, and recycled products. Employing a qualitative-descriptive approach, digital search footprints are analyzed as a proxy for consumer intention and behavioral shifts. The findings reveal a significant upward trajectory, marking a transition from niche curiosity to mainstream demand. The trend evolved through three phases: a health-centric surge triggered by the COVID-19 pandemic (2020–2021), a lifestyle diversification into ethical fashion and zero-waste kits (2022–2023), and a normalization phase (2024–2025) where sustainability became a standard consumer expectation. While global climate events and government policies acted as catalysts for search spikes, economic fluctuations remained a primary driver for behavioral shifts toward affordable sustainable alternatives. The study concludes that "green" consciousness in Indonesia is no longer a temporary trend but a permanent cultural shift. Methodologically, the research proves that big data analytics provides a more dynamic and efficient understanding of consumer psychology than conventional surveys. These results offer critical insights for businesses and policymakers to align their strategies with the increasingly ethical and digital-native Indonesian market.